2011
DOI: 10.1016/j.chb.2010.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge hoarding and user acceptance of online discussion board systems in eLearning: A case study

Abstract: This paper aims to reveal the determinants of the effectiveness of online discussion board systems (ODBSs) in eLearning environments to foster the interactions among the learners and/or instructors. A case in which an ODBS failed to foster the interactions among learners / instructors for knowledge sharing is introduced and hypotheses to explain the failure are developed based on thorough literature review in technology acceptance model (TAM) and knowledge hoarding. The hypotheses are tested via statistical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 23 publications
0
29
0
1
Order By: Relevance
“…Lee et al (2011) found that obtaining and maintaining a sufficient level of network externalities is one of the success factors in the data collected from a questionnaire survey of 78 students.…”
Section: Literature Review Of Criteria For It Tool Selection In E-leamentioning
confidence: 99%
“…Lee et al (2011) found that obtaining and maintaining a sufficient level of network externalities is one of the success factors in the data collected from a questionnaire survey of 78 students.…”
Section: Literature Review Of Criteria For It Tool Selection In E-leamentioning
confidence: 99%
“…Referring to Lee et al (2011), learning achievement is learners' physical and mental interaction with environments. There are lots of factors in learning achievement.…”
Section: Learning Achievementmentioning
confidence: 99%
“…Referring to Lee et al (2011), learning achievement is divided into (1)high learning achievement and (2)low learning achievement.…”
Section: Learning Achievementmentioning
confidence: 99%
“…A successful online discussion has the same synergistic effect of group discussion, in which people build on one another's perspectives to gain a deeper understanding of the topics (Gonzalez-Bailon et al, 2010;Prabowo et al, 2008). In recent, a web-based online discussion forum is a vast repository of consumers' knowledge and opinions, and they can face with many issues such as firm behavior or moreover firm crisis through online channel (Lee et al, 2011;Lu et al, 2011). In our research, we are likely to focus on public firms' information through online space such as crisis-related public relation for managerial implication and improvement of social welfare.…”
Section: Introductionmentioning
confidence: 99%